Global curriculum in research literacy for the surgical oncologist. Issue 1 (January 2018) - Are, C.; Yanala, U.; Malhotra, G.; Hall, B.; Smith, L.; Cummings, C.; Lecoq, C.; Wyld, L.; Audisio, R.A.; Berman, R.S.
Abstract: Background: The ability to provide optimal care to cancer patients depends on awareness of current evidence-based practices emanating from research or involvement in research where circumstances permit. The significant global variations in cancer-related research activity and its correlation to cancer-specific outcomes may have an influence on the care provided to cancer patients and their outcomes. The aim of this project is to develop a global curriculum in research literacy for the surgical oncologist. Materials and Methods: The leadership of the Society of Surgical Oncology and European Society of Surgical Oncology convened a global curriculum committee to develop a global curriculum in research literacy for the Surgical Oncologist. Results: A global curriculum in research literacy is developed to incorporate the required domains considered to be essential to interpret the published research or become involved in research activity where circumstances permit. The purpose of this curriculum is to promote research literacy for the surgical oncologist, wherever they are based. It does not mandate direct research participation which may not be feasible due to restrictions within the local health-care delivery environment, socio-economic priorities and the educational environment of the individual institution where they work. Conclusions: A global curriculum in research literacy is proposed which may promote research literacy or encourage involvement in research activity where circumstances permit. It is hoped that this will enhance cancer-related research activity, promote awareness of optimal evidence-based practices and improve outcomes for cancer patients globally. Abstract : Synopsis: The proposed global curriculum in research literacy developed by the Society of Surgical Oncology and the European Society of Surgical Oncology may promote research literacy and improve the care and outcomes of cancer patients globally.